Teacher Pedagogic Competence in Improving Arabic Language Learning Outcomes Based on Curriculum Integration - Suci Ramadhanti Febriani; Rahmawati Rahmawati; Muhammad Afif Amrulloh; Kddour Guettaoui Bedra (UIN Sultan Aji Muhammad Idris Samarinda, 2023)
The teacher's pedagogical competence influences the use of strategies and the ability to manage the learning system in the classroom. This encourages teachers' efforts to have pedagogical competence in carrying out learning activities optimally. Integrating the Ministry of Religion and the Diniyyah Arabic Center (DAC) curriculum is the basis for strengthening teachers’ pedagogical competence. On that basis, this study aims to identify the pedagogic competence of teachers based on integrating the Ministry of Religion curriculum and the Diniyyah Arabic Center curriculum (DAC) at Diniyyah Puteri Padang Panjang. This research is based on a descriptive qualitative approach by identifying the implementation of teaching competencies based on integrating the Arabic language curriculum at Diniyyah Puteri Padang Panjang. The results showed that the implementation of the teacher's pedagogic competence in improving Arabic learning outcomes was obtained through: (1) identifying priority learning objectives, (2) implementing a learning system according to the order and needs of the learner, and (3) evaluating the learning system periodically. The findings indicate that the pedagogic competence of teachers can encourage an increase in Arabic language skills based on curriculum integration at Diniyyah Puteri Padang Panjang.